Some early Indian amphibian illustrations and their artists - Das, I.; Dutta, S. (Wildlife Institute of India, 2017)
Amphibians researchers will benefit from examination of early works, including books and papers by nineteeth century zoologists, most of which are illustrated with black and white or hand coloured lithographic or engraved images of the subject. This essay deals with selected works from the period, and discusses such artwork and their artists and authors.